Urgensi Nilai-nilai Moderasi Qur’ani dalam Pendidikan - Sofyan, Achmad Sofyan Sauri (UIN Kiai Haji Achmad Siddiq Jember, 2024)
Abstrak Education as an instrument for delivering education to students occupies a quite urgent position in instilling important aspects related to moderation, so that by embedding good potential on the basis of moderation an ideal life will also be created. The method in this study is thematic qualitative, with a problem formulation, 1) the conception of Qur'anic moderation. 2) the urgency of moderation in education as an effort to produce a tolerant generation. Moderation is an effort to make social life ideal, a condition of mutual respect for one another by considering differences. On the other hand, differences are not used as obstacles to a harmonious life, but rather become an instrument towards the common good. The Qur'anic values ​​of moderation have the potential to make human social life conform to their nature, namely the conditions in their lives. There is an important principle in Koranic moderation, namely respect for differences, both in the context of culture, language, skin color, and even belief. Respect for these differences is the main foundation for realizing an ideal life.